Meta Analysis of Profitability Islamic Banking Research - Sofina Mujadiddah; Diah Munawaroh; Yuyun Ma’rifatul Inayah (IAIN Kudus, 2022)
Islamic banks are financial institutions whose operations and products are developed based on the Al-qur’an and Hadith. One of the most important things in banking is profitability. Islamic bank profitability studies are important tools for improving performance, evaluating bank operations and determining management plans to help increase the chances of a bank surviving in a competitive market. Therefore, this study aims to determine the map of research development related to the Profitability of Islamic Banking using the Meta Analysis approach. This research method uses purposive non probability sampling method, using descriptive statistics in the explanation. The data used in this study are 100 international and local journals issued from various accredited journals with the theme of profitability of Islamic banking during the 2010-2020 period. This study experienced an increase and decrease in the number of journals during 2010-2020, and the largest number of authors who discussed the theme of the profitability of Islamic banking were 2 journals. In addition, journals that publish papers on the theme of profitability are the International Journal of Economics and Financial Issues, with a total of 6 papers. During this research, the most widely used method is the quantitative method with the model used is the analysis panel data. During this study, the journal by Dietrich and Wazenried (2011) was the study with the most citation as many as 878.